Does the CFO serving as the secretary of the board affect the financial statement comparability?—evidence from China. Issue 3 (March 2023) - Wang, Yueyun; He, Zhenhua; Huang, Yihan; Li, Chenhang
Abstract: One person serving as both CFO and board secretary is a unique institutional feature in China. Individuals in this senior executive role are responsible for not only the preparation of financial statements but also the coordination of information disclosure. We investigate the relation between a CFO serving as board secretary and financial statement comparability. We find that a CFO serving as board secretary improves the comparability of a firm's financial statements in additional analysis. This positive effect is more significant when the CFO is female or middle-aged, or has a Bachelor's degree or higher or a financial background. This paper enriches the theoretical research on CFO's employment characteristics and the quality of financial reports, and provides reference value for improving the quality of financial reports.